2021
DOI: 10.1038/s41438-021-00564-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and physiological analyses provide insights into the leaf epicuticular wax accumulation mechanism in yellowhorn

Abstract: Plantations and production of yellowhorn, one of the most important woody oil and urban greening trees widely cultivated in northern China, have gradually become limited by drought stress. The epicuticular wax layer plays a key role in the protection of yellowhorn trees from drought and other stresses. However, there is no research on the mechanism of wax loading in yellowhorn trees. In this study, we investigated the anatomical and physiological characteristics of leaves from different germplasm resources and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…As expected, MT plants were much more tolerant to drought stress than WT plants, as indicated by their fewer wilting leaves under drought stress ( Figure 4 A–D). This result supported previous reports, which suggested that high cuticular wax deposition could improve plant tolerance to drought stress [ 5 , 28 , 34 , 35 ]. Proline and soluble sugar acted as compatible osmolytes involved in plant response to drought stress [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…As expected, MT plants were much more tolerant to drought stress than WT plants, as indicated by their fewer wilting leaves under drought stress ( Figure 4 A–D). This result supported previous reports, which suggested that high cuticular wax deposition could improve plant tolerance to drought stress [ 5 , 28 , 34 , 35 ]. Proline and soluble sugar acted as compatible osmolytes involved in plant response to drought stress [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The epidermal wax layer plays an important role in plant resistance to stress, especially drought stress. One KCS gene was differently expressed in yellow horn with different leaf wax thickness and showed a coexpression correlation with some transcription factors (e.g., MYB3) [16]. In this study, in order to further explore the role of KCS genes in the resistance response of yellow horn, bioinformatics methods were used to identify the members of the KCS gene family of yellow horn and the tissue expression patterns and expression level under abiotic stress were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely adaptable to various growth conditions, such as drought, low temperature, salt, alkali, and other conditions [2,3]. It is one of the most important species of woody oil [4]. The oil content of its seed kernel can be as high as 67%, of which 85-93% is unsaturated fatty acids, including 37.1-46.2% linoleic acid and 28.6-37.1% oleic acid, which are essential dietary fatty acids [5].…”
Section: Introductionmentioning
confidence: 99%